Peran Guru Dalam Memotivasi Untuk Meningkatkan Kualitas Belajar Siswa Berbasis UPTD di (SD) Sekolah Dasar Negeri 71 Barru - Muhammad Saadam Sadiq; Abdul Sadiqin Sadiq; Jumaidah Jumaidah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to determine the extent of the teacher's role in motivating to improve the quality of UPTD-based student learning at the 71 Barru State Elementary School (SD). Barru Regency, South Sulawesi. This research method uses qualitative with a purposive sampling technique based on needs with a sample of 10 teachers. The research design was carried out based on the Creswell 1996 setting. The results obtained are that the role of the teacher is an important role in improving teaching and guiding if teaching is processing people to become smart, intelligent, clever. Guiding means activities that require students to develop in providing an environment and direction that is in accordance with educational goals. Motivation as a teacher is important because improving the quality of education is a requirement to accelerate the realization of a democratic society. And the quality of student learning is important in improving student achievement.